2019
DOI: 10.1177/1071100719893699
|View full text |Cite
|
Sign up to set email alerts
|

Deep Peroneal Nerve Injury Following Hardware Removal for Lisfranc Joint Injury

Abstract: Background: Surgical exposure of the Lisfranc joint complex is within close proximity to the deep peroneal nerve, which can be injured in this approach. Common clinical practice is to remove Lisfranc hardware at 3 to 4 months postoperatively. However, it is unknown if this provides a clinical benefit or risks injury to the deep peroneal nerve. The rate of nerve injury is currently unknown from the published literature. This study clarifies rates of neurological injury to the deep peroneal nerve during primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Another recent study of a single-surgeon case series reported on the rates of nerve injury complications, specifically of the primary fixation and of the subsequent planned surgery to remove metalwork 3-4 months later. This showed an overall nerve injury rate of 23% when routine metalwork removal was planned, 21 consistent with the results of this review.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Another recent study of a single-surgeon case series reported on the rates of nerve injury complications, specifically of the primary fixation and of the subsequent planned surgery to remove metalwork 3-4 months later. This showed an overall nerve injury rate of 23% when routine metalwork removal was planned, 21 consistent with the results of this review.…”
Section: Discussionsupporting
confidence: 89%
“…In keeping with recent studies, 12,21 this review found that when planned, metalwork removal was scheduled most commonly at 3-4 months post fixation. The absence of justification found for the timing of metalwork removal, and variation in current practice, 31 further supports the notion of true equipoise regarding Lisfranc metalwork management.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…e Lisfranc joints play an important role in connecting the forefoot and midfoot and maintaining the stability of the arch of the foot [1][2][3]. With the rapid development of transportation and construction industry in recent years, the incidence of Lisfranc injury has been increasing year by year, and if not treated in time, it will lead to poor walking, pain in the back of the foot, and even disability in severe cases [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…DPN unveiled in this study can also correlate to clinical imaging information 32,33 and be used to predict clinical neurovascular consequences following a traumatic injury or treatment in the ankle and foot region. 34…”
Section: Discussionmentioning
confidence: 99%